The impact of the COVID-19 shock on euro area potential output: A sectoral approach - Nicolò Bandera; Katalin Bodnár; Julien Le Roux; Bela Szörfi (European Central Bank (ECB), 2022)
The COVID-19 crisis has affected economic sectors very heterogeneously, with possible risks for permanent losses in some sectors. This paper presents a sectoral-level, bottom- up method to estimate euro area potential outputin order to assess the impact of the crisis on it. The estimates are based on a supply-demand shock decomposition and are meant to quantitatively support theestimation of scarring effectsstemming from the pandemic. The results show that sectors of "trade, transport and accommodation", "other services" and "industry" may suffer a loss in trend output ofaround 1.4-1.6% by 2025. Aggregate potential output in 2025 mightbe about 0.8% lower than it would have been without the crisis, and importantly, without support from the Next Generation EU (NGEU), signalling somewhat larger losses than embedded in theAutumn 2021 forecast of the European Commission (which takes the NGEU into account).
Keywords: C32; D24; E32; E37; 330; COVID-19; forecasting; production function; potential output; sectoral approach